Respuesta :

Answer:

sec x.

Step-by-step explanation:

cos( - x) + tan( – x)sin( – x)

= cos(-x) + sin(-x)sin(-x) / cos(-x)

= cos(-x)(cos(-x)  + sin^2x / cos(-x)

= (cos^2x + sin^2 x) / cos(-x)

= 1 / cos(-x)

= 1 /cos x

= sec x.

= sec (-x).

Answer:

sec x

Step-by-step explanation:

cos (-x) = cos x (even function)

tan (-x) = -tan x = -sin x / cos x

sin (-x) = - sin x (odd function)

Then:  cos( - x) + tan( – x)sin( – x) becomes:

                              sin x        -sin x    

           cos(x)    - ------------ * -----------

                              cos x           1

or

            cos²x         sin²x               1

          ------------ + ------------ = --------------- = sec x (answer)

             cos x            1               cos x

ACCESS MORE